A low‐cost high‐gain dual polarized antenna design from cuboids and shorting strips for base stations. Issue 11 (25th July 2019) - Yadav, Subash Chandra; Duttagupta, Siddhartha P.; Atmakuru, Nagaraju
Abstract: This article presents a novel low‐cost high‐gain dual‐polarized antenna using suspended cuboid and ground connected cuboid geometry. The design structure of the antenna is simple and it's all components are fabricated by a copper sheet of thickness 0.5 mm. The prototype is fabricated and measured and has −15 dB impedance bandwidths of 33.33%(2.5‐3.5 GHz) with broadside gain of 9.2 ± 0.3 dBi and 32.25%(2.6‐3.6 GHz) with broadside gain 9 ± 0.3 dBi over bandwidths when measured from port 1 and port 2, respectively. The isolation between the ports is enhanced by shorting suspended cuboid from the ground plane and measured one more than 17 dB from 2.45 to 3.7 GHz. The proposed dual polarized antenna can be used for base stations such as Wireless Local Area Network (WLAN), Long Term Evolution (LTE), and Worldwide Interoperability for Microwave Access (WiMAX) applications. The antenna is designed and simulated and there are good agreements between simulated and measured results are obtained.